Nature Exploitation in Guntur Alam’s Short Story Harimau Belang: An Ecocritical Perspective - Nasution, Cherry Adistya; Balqis, Kesya Aprillia; Rahma, Risky Kartika; Wahyuni, Sari Indah; Purwarno, Purwarno (ITScience (Information Technology and Science), 2024)
Guntur Alam, a distinguished literary figure from South Sumatra, delves into environmental exploitation in his acclaimed short story, Harimau Belang. This study employs a descriptive qualitative method and literary ecocriticism to dissect the intricate relationship between humans and nature depicted in Alam's narrative. The research explores three environmental themes—deforestation, river water pollution, and coal mining—illuminating the repercussions of human activities on the natural environment. Through evocative imagery and character experiences, the study underscores the pressing need to preserve ecosystems and adopt sustainable practices. The narrative serves as a rallying cry, urging readers to contemplate the ethical and environmental consequences of resource exploitation and advocate for responsible environmental stewardship. Overall, this research demonstrates that Harimau Belang offers a poignant examination of humanity's environmental footprint, emphasizing the imperative of sustainable practices for the well-being of future generations.